Analisis Area Jangkauan dan Rute Tercepat Menuju Pusat Fasilitas Kesehatan di Kota Denpasar - Tugma Jaya Manalu; Martina Ayu Sejati; Poppy Haryani (MASALIQ, 2025)
Fast and accurate healthcare services, particularly in emergency situations, are highly influenced by the effectiveness of access to health facilities. Therefore, geographic accessibility becomes a key factor in improving both the accessibility and quality of services for the community. This study aims to map service coverage areas and determine the fastest routes to healthcare facilities in Denpasar City. The method employed is Network Analysis based on Geographic Information Systems (GIS), using QGIS 3.6 software. The analysis results indicate that there are 23 healthcare facilities evenly distributed across all subdistricts, all located within a 5 km radius of Sanglah Hospital. Distances to Sanglah Hospital range from 0.4 to 5 km, with estimated travel times between 0.48 and 6 minutes. The nearest facilities are RS Medika Prima II and RS Surya Husadha, located 0.4 km away with an estimated travel time of approximately 0.48 minutes, while RS Bhakti Rahayu is the farthest, at a distance of 5 km and a travel time of approximately 6 minutes. These findings provide important implications for evacuation route planning and the enhancement of spatially based emergency healthcare systems.